Prevalence, pathogenic bacteria, and risk factors associated with pediatric sepsis among under five children in a rural district hospital in Rwanda - Patrick Orikiriza; Deogratius Ruhangaza; David S. Ayebare; Ezechiel Bizimana; Jean Baptiste Niyibizi; Irene Nshimiyimana; Louis Mujyuwisha; Abebe Bekele (PLoS ONE, 2025)
Background Pediatric sepsis poses a significant health challenge in Sub-Saharan Africa, with limited data on prevalence and pathogen profiles. This study determined the prevalence of pediatric sepsis, identified bacterial pathogens, and evaluated associated risk factors among children aged 1–59 months at Butaro Hospital, Rwanda. Methods A cross-sectional study was conducted from March 2022 to December 2022. The study included 114 children aged 1–59 months with suspected sepsis admitted to the pediatric ward at Butaro Hospital. Blood cultures were analyzed, and risk factors assessed using multiple logistic regression. Data were analyzed using Stata 17. Results Of 114 enrolled children, 60.5% (n = 69) had positive blood cultures (95% CI: 51.2–69.1). Among these 69 children, the majority were females, 70.0% (n = 35) (95% CI: 53.7–81.3) and below 6 months 68.1% (n = 15) (95% CI: 45.3–84.7). Pathogenic bacteria identified were Coagulase-Negative Staphylococci (CNS), 59.4% (n = 41) and Staphylococcus aureus, 40.6% (n = 28). Female gender (AOR = 2.4, 95% CI: 1.0–5.4, p = 0.045) and leukocytosis (AOR = 6.0, 95% CI: 2.0–20.2, p = 0.003) were the risk factors for sepsis. Conclusions The study reveals a high prevalence of sepsis among children under-five, especially females and less than 6 months with female gender and diagnosis with leukocytosis being a significant risk factor. Diagnostic strategies should focus on WBC counts to better manage at-risk children. These single-center study results however may not be broadly representative due to regional and resource differences, but they offer valuable insights for improving pediatric care in similar low-resource settings.